The types of illocutionary acts found in lean on me movie - Rolandi, Alexandro; Utami, Ni Made Verayanti; Juniartha, I Wayan (Journal of Language and Applied Linguistics, 2022)
This study aimed at identifying the types illocutionary acts found in a movie entitled Lean On Me. The problems of this study is What types of illocutionary acts are found in the movie entitled Lean On Me?. This study employed descriptive and qualitative method to provide a well-organized description regarding the problems being identified. The data of this study were obtained by observation method through five steps, namely watching the Lean On Me movie. Then, finding out the movie script of Lean On Me. Furthermore, the writer read the movie script and took note of the illocutionary acts spoken by the characters in the movie Lean On Me. Eventually, the writer classified the data collected. There were five types of illocutionary act encountered they are, assertive, directive, commissive, expressive, and declarative. The result of the research indicates that there are 9 data of illocutionary act found in Lean On Me movie covering 2 assertive, 3 directive, 2 commissive, 1 expressive, and 1 declarative.